Models to estimate the bunch dry weight in african oil palm (elaeis guineensis jacq.), american oil palm (elaeis oleifera h.b.k. cortes) and the interspecific hybrid (e. oleifera x e. guineensis) (2012)
Statistical models were used to estimate the bunch dry weight through indirect nondestructive methods in African oil palm (Elaeis guineensis) American oil palm (Elaeis oleifera) and the interspecific hybrid (E. oleifera x E. guineensis); and compared with the formula proposed by Corley. The studies were conducted at Santa Barbara and Chaparral-Cuernavaca on the Unipalma plantation, located in the eastern palm region of Colombia. Ten palms were selected for each group and 30 bunches were sampled for six months. Polynomial and exponential statistical models were postulated, with the best being linear without intercept. The results confirm and validate the usefulness of the model formulated to estimate the bunch dry weight of African oil palm (E. guineensis), American oil palm (E. oleifera) and the interspecific hybrid (OxG); however, it proved more convenient to use the models proposed in this study because they are tailored to the specific environmental conditions of the eastern palm region of Colombia.